Stateness and democracy: evidence from East Asia and cross-regional comparisons - Croissant, Aurel; Hellmann, Olli (Stateness and democracy in East Asia, 2020)
The concluding chapter summarizes and synthesizes findings across the different country. This exercise reveals two key points regarding the state-democray nexus. First, stateness is neither a sufficient nor a necessary condition for democratic consolidation. Not only can newly democratising regimes be subject to path-dependent effects but intervening variables - in particular, the organization of particularistic networks - also play a role. Second, democracy will only have a strengthening effect on stateness if all partial regimes are sufficiently consolidated. That is to say, defective democracies do not produce strong incentives for political elites to invest in state-building. These findings are placed in a comparative perspective with ‘third-wave’ democracies in other parts of the world, which shows that our causal mechanisms travel beyond East Asia.
Gesehen am 22.04.2021